The Concept of Family Hadis Madrasah In Yaman With The Form Of Sanadisation Of Musalsal Bi Al-Yamaniyin Hadiths - Fajrurrohman, Fajrurrohman; Solihah, Siti Rohmah Fitria; Yordan, Andika Yusuf; Wiwaha, Rizzaldy Satria; Kosasih, Engkos (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Musalsal hadith is one model of hadith transmission from the time of the Prophet Muhammad to narrators from generation to generation, even today. In this study, the authors found a unique concept of sanadization, namely the Sanadization of the Hadith Musalsal bi Al-Yamaniyin, or the form of sanad, which is the custom of a family in Yemen. Therefore, this study aims to trace the examples of sanadization that the researcher mentioned earlier. In this study, the authors used a qualitative research method with a type of library research, with a regional hadith study approach. This research found that the people of Yemen strictly guard against Islamic knowledge, especially in the transmission of hadiths, so there is a habit of transmitting hadiths by information from close family members. In this study, the authors took a sample from the traditions they carried out with sufficient sanadization to maintain an intellectual level among their families.